1,2,4,5-Tetraphenyl-1H-imidazole - Bing Zhao; Zhi-yu Li; Meng-jiao Fan; Bo Song; Qi-gang Deng (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, C27H20N2, contains two independent molecules, A and B. In both molecules, the N atom in the 1-position and the C atom in the 5-position are statistically disordered [as 0.571 (8):0.429 (8) in A and 0.736 (9):0.264 (9) in B]. The phenyl rings in the 1-, 2-, 4- and 5-positions in A are twisted from the central imidazole ring by 84.3 (2), 21.6 (2), 21.5 (2) and 75.7 (2)°, respectively. The corresponding dihedral angles in B are 85.5 (2), 3.8 (2), 2.4 (2) and 81.7 (2)°, respectively.